2007
DOI: 10.1038/sj.mt.6300128
|View full text |Cite
|
Sign up to set email alerts
|

Carrier Cell–mediated Delivery of a Replication-competent Adenovirus for Cancer Gene Therapy

Abstract: Although replication-competent viruses have been developed to treat cancers, their cytotoxic effects are insufficient, as infection is inhibited by the generation of neutralizing antibodies. To address this limitation, we developed a carrier cell system to deliver a replication-competent adenovirus. Carrier cells infected with replication-competent adenovirus were incubated with target cancer cells in a high titer of anti-adenovirus antibody. Carrier cells were injected into syngeneic subcutaneous tumors after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(63 citation statements)
references
References 19 publications
1
62
0
Order By: Relevance
“…Previous studies with replication-competent adenovirus-infected carrier-cell systems have reported the use of wild-type HAd5 adenovirus-infected MDA-MG-231 cells 30 and also of granulocyte-macrophage colonystimulating factor-expressing HAd5 loaded into A549 and 293 cells. 10 In this last work, Hamada et al 10 reported that bystander transfection was mediated by carrier-cellderived cell fragments containing viral particles that were engulfed by proliferative target cancer cells. This engulfment-mediated transfer of adenovirus was not inhibited by anti-adenovirus antibodies and enabled repetitive infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies with replication-competent adenovirus-infected carrier-cell systems have reported the use of wild-type HAd5 adenovirus-infected MDA-MG-231 cells 30 and also of granulocyte-macrophage colonystimulating factor-expressing HAd5 loaded into A549 and 293 cells. 10 In this last work, Hamada et al 10 reported that bystander transfection was mediated by carrier-cellderived cell fragments containing viral particles that were engulfed by proliferative target cancer cells. This engulfment-mediated transfer of adenovirus was not inhibited by anti-adenovirus antibodies and enabled repetitive infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, such modifications were ineffective in the case of third or later injections, owing to an increase in anti-adenovirus antibody titer, and, therefore, could not produce significant antitumor effects. 10 Almost all dogs have circulating anti-CAV antibodies and T-lymphocytes developed as a result of immunization or natural infection. Two serotypes of CAV have been described in dogs: CAV1 and CAV2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, the immune system is by passed by viruses that are camouflaged under a different capsid or shielded with chemical compounds like polyethylene glycol in order to "trick" the immune system and be deliver to the tumor site. Stem cells, cancer stem cells, endothelial cells and progenitors, immune cells and even cancer cells as carriers have been, or are being tested for their efficacy and proof of principle (Iguchi et al, 2012;Hamada et al, 2007;Stoff-Khalili et al, 2007). Another approach to overcome the pre-existing immunity is the temporal immunosuppression using pharmacologic interference to bypass the adaptive and innate immune response.…”
Section: Hurdles For the Use Of Viruses As Delivery Vectorsmentioning
confidence: 99%
“…[8][9][10] In order to overcome these drawbacks, CRAds have been delivered to target cells in vivo using CRAd-infected mesenchymal stem cells or tumor cells as vector. [11][12][13][14][15] In this strategy, cells infected with CRAds are termed 'carrier cells' and use of these cells allows the CRAds to bypass the pre-existing anti-Ad antibodies. 11,15 In addition, use of carrier cells significantly reduces the accumulation of Ad vectors in the liver, because Ad capsid proteins, which are responsible for liver accumulation, are not exposed to the outside of the carrier cells.…”
Section: Introductionmentioning
confidence: 99%